Analisis kinerja keuangan menggunakan metode Economic Value Added (EVA) dan Market Value Added (MVA) pada PT. Telekomunikasi Indonesia (Persero) Tbk. dan PT. Indosat Tbk. periode 2013-2017 - Mella Eka Crysdayanti (STIE Perbanas Surabaya, 2017)
This study on the financial performance of companies was done using EVA and MVA, and this is is a case study using the company's financial statements with its calculations. This research objective is to measure and compare the financial performance of PT Tele-komunikasi Indonesia, Tbk, and PT Indosat Tbk in the period 2013-2017 through using EVA dan MVA. From the research result using Economic Value Added (EVA) and Market Value Added (MVA) approach, obtained results that PT Telekomunikasi Indo-nesia, Tbk is a company that can provide the value of a positive EVA (EVA>0) for five years in a row and give the stock market a positive value indicated by the value of the MVA is positive (MVA>0) in 2013-2017. Followed by PT Indosat, Tbk are only able to provide the value of a positive EVA (EVA>0) by 2016-2017 and give a positive Market Value Added (MVA>0) an annual period of 2013-2017.